Comparative Treatment Patterns and Outcomes of Fulvestrant versus Everolimus Plus Exemestane for Postmenopausal Metastatic Breast Cancer Resistant to Aromatase Inhibitors in Real-World Experience - Li Y; Xie Y; Gong C; Zhao Y; Zhang J; Zhang S; Wang L; Chen S; Hu X; Wang B (Dove Medical Press, 2020)
Yi Li,1,* Yizhao Xie,1,* Chengcheng Gong,1 Yannan Zhao,1 Jian Zhang,1 Sheng Zhang,1 Leiping Wang,1 She Chen,2 Xichun Hu,1 Biyun Wang1 1Department of Medical Oncology, Fudan University Shanghai Cancer Center, Department of Oncology, Shanghai Medical College, Fudan University, Shanghai 200032, People’s Republic of China; 2Key Laboratory of Glycoconjugate Research Ministry of Public Health, Department of Biochemistry and Molecular Biology, School of Basic Medical Sciences, Fudan University, Shanghai 200032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Biyun Wang; Xichun HuDepartment of Medical Oncology, Fudan University Shanghai Cancer Center, #270 Dongan Road, Xuhui District, Shanghai 200032, People’s Republic of ChinaEmail wangbiyun0107@hotmail.com; huxichun2017@163.comBackground: Fulvestrant (FUL) and the combination of everolimus and exemestane (EVE-EXE) were the options to treat hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) metastatic breast cancer (MBC) patients who were refractory to aromatase inhibitors (AIs). The practical knowledge of treatment patterns and outcomes between the two regimens is essential for improving treatment decisions.Methods: HR+/HER2− MBC patients, who were refractory to AI, were treated with FUL or EVE-EXE from June 2013 to June 2016 were included. Treatment patterns, progression-free survival (PFS), overall survival (OS), and toxicity were reported. Propensity score matching (PSM) was used to minimize potential confounders.Results: A total of 168 patients were enrolled. Of 168 patients, 124 patients were treated with FUL and 44 patients received EVE-EXE. Patients who were treated with EVE-EXE were younger, more likely to have visceral, liver, multiple sites of metastases, and had received more prior chemotherapy. After adjusting for propensity score matching (PSM), no significant difference in PFS was found between two groups (P=0.419). However, in the subgroup of multiple metastatic sites, the median PFS was significantly improved in the EVE-EXE arm compared with FUL arm (6.1 vs 3.2 months, respectively, P=0.012). More patients in EVE-EXE arm discontinued treatment due to adverse events than in the FUL arm.Conclusion: A substantial difference in treatment patterns was observed between the two arms. Clinical outcomes were comparable after PSM.Clinicaltrials.gov Identifier: NCT03695341 (May 14, 2018).Keywords: fulvestrant, everolimus, exemestane, metastatic breast cancer, endocrine therapy